2017
DOI: 10.1186/s12940-017-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of exposure to static electric fields in humans and vertebrates: a systematic review

Abstract: BackgroundHigh-voltage direct current (HVDC) lines are the technology of choice for the transport of large amounts of energy over long distances. The operation of these lines produces static electric fields (EF), but the data reviewed in previous assessments were not sufficient to assess the need for any environmental limit. The aim of this systematic review was to update the current state of research and to evaluate biological effects of static EF.MethodsUsing the PRISMA (Preferred Reporting Items for Systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…The SEF intensity of 27.5 kV/m was close to the exposure limits of SEF specified in existing local or industry standards 6 , 7 , 19 ; 34.7 kV/m was almost the maximum intensity of SEF in the vicinity of ground generated by actual UHVDC transmission lines 3 5 ; 56.3 kV/m was a relatively high intensity and was about 2 times higher than the minimum intensity used in this study. Furthermore, results also showed that with the increase of voltage applied between two electrodes, the intensity of SEF inside the cages of sham exposure group had almost no change and the intensity was 0.28 ± 0.01 kV/m, which was close to the background level of SEF (0.1~0.3 kV/m) 20 .…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…The SEF intensity of 27.5 kV/m was close to the exposure limits of SEF specified in existing local or industry standards 6 , 7 , 19 ; 34.7 kV/m was almost the maximum intensity of SEF in the vicinity of ground generated by actual UHVDC transmission lines 3 5 ; 56.3 kV/m was a relatively high intensity and was about 2 times higher than the minimum intensity used in this study. Furthermore, results also showed that with the increase of voltage applied between two electrodes, the intensity of SEF inside the cages of sham exposure group had almost no change and the intensity was 0.28 ± 0.01 kV/m, which was close to the background level of SEF (0.1~0.3 kV/m) 20 .…”
Section: Methodsmentioning
confidence: 54%
“…The indirect influence of surface charges, such as piloerection and cutaneous stimulation, is another possible explanation of SEF biological effects 20 . When organisms were exposed to SEF, not only polarized charges will come into being on the surface of skin but also charged ions in body fluids will migrate directionally to the surface of skin.…”
Section: Discussionmentioning
confidence: 99%
“…It is indeed surprising that greater attention was not given by investigators to the confounding effects of electric fields from corona ion generators since a static electric field is known to be a mechanosensory stimulus to hair on the body surface. Recent systematic reviews of static-field research on vertebrates and invertebrates have confirmed that superficial sensory stimulation by static electric field is the mechanism by which static electric fields produce behavioral and physiological effects in humans, animals, and plants [ 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lv X, et al, 2014, proved that exposure to the 0.86 μT magneticfield did not cause problems on the patient's blood vessels. Petri et al, 2017, stated that exposure to static magnetic fields is not proven to cause biological effects .…”
Section: Discussionmentioning
confidence: 99%